Analisis Kompetensi dan Etika Pendidik dalam Perspektif Profesionalisme Guru - Kharismatul Khasanah; Nisfu Istiqomah; Akmal, Maulidina; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Improving the quality of education cannot be separated from the role of teachers as the primary actors in the learning process. However, various issues such as low-quality instruction, suboptimal mastery of technology, and weak application of ethical values, remain challenges in fostering teacher professionalism. This study aims to examine teacher professionalism through the relationship between competencies and professional ethics. This study employs a literature review method with a descriptive qualitative approach, involving the collection and analysis of relevant scientific sources. The findings indicate that competencies and ethics have a complementary relationship in shaping teacher professionalism. Competencies provide the foundational skills for carrying out instructional tasks, while ethics serve as a moral guide for fulfilling those roles responsibly. Without a balance between the two, the educational process risks losing its direction, both in terms of effectiveness and humanistic values. Therefore, teacher professionalism must be developed by strengthening competencies in alignment with the application of ethical values in educational practice. Keywords: Steacher professionalism, competencies, professional ethics, education.